Empirical Finance Modelling and Analysis of Emerging Financial and Stock Markets - Islam, Sardar M. N.; Watanapalachaikul, Sethapong (Contributions to Economics,, 2005)
The emphasis of this book is on understanding special characteristics of the financial systems of emerging markets, where the existence of market imperfections such as asymmetric information, adverse selection and moral hazard can cause financial market failures. Considering the Thai stock market as an example, this book provides an econometric study of a typical Asian financial system. Many contemporary techniques and models are used in this study, including simple multivariate regression, multi-factor model, exponential smoothing, Holt Winter's models, and GARCH type models. The findings of the existence of rational bubbles, anomalies, volatility and other characteristics reveal evidence of inefficiency in the Thai stock market. Based on these results, the book includes justifications for public policies in such economies and makes suggestions for further research areas.